Ternary iron-based oxygen carrier with core-shell structure as well as preparation method and application of ternary iron-based oxygen carrier

By using a core-shell structure ternary iron-based oxygen carrier in chemical chain hydrogen production, the LaFeO3-ZrO2 shell of the Fe2O3 core body is solved, and the hydrogen production efficiency and cycle stability are improved , high hydrogen yield and anti-sintering performance are achieved.

CN119143080APending Publication Date: 2024-12-17NANJING NORMAL UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410670913.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the hydrogen production process of chemical chains, the iron ion migration and enrichment of iron-based oxygen carriers leads to sintering problems, affecting hydrogen production efficiency and cycling stability.

Method used

The ternary iron-based oxygen carrier is adopted for core-shell structure, and the quasi-nano-scale Fe2O3 core is coated through the LaFeO3-ZrO2 shell. The anti-sintering ability of ZrO2 and the oxygen ion conduction ability of LaFeO3 are used to inhibit Fe ion migration and enrichment and improve oxidation. Reduction reaction activity and cycle stability.

Benefits of technology

The anti-sintering ability and circulation stability of iron-based oxygen carriers were significantly improved, the hydrogen yield was increased by 41.6%, and high reactivity and anti-charcoal accumulation ability were maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143080A_ABST
    Figure CN119143080A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary iron-based oxygen carrier with a core-shell structure as well as a preparation method and application of the ternary iron-based oxygen carrier. The particle size of the ternary iron-based oxygen carrier with the core-shell structure is 150-350 [mu] m, and a core is a quasi-nano particle and is formed by compounding Fe2O3, ZrO2 and LaFeO3 according to the mass ratio of 6: 1: 3. The preparation method comprises the following steps: dissolving a water-soluble salt of a shell material in deionized water to obtain a mixed solution, stirring and heating, dropwise adding a calculated amount of citric acid, and heating the mixed solution to obtain a chelating solution; the preparation method comprises the following steps: preparing nuclear material quasi-nano-particles by a coprecipitation method, dispersing the nuclear material quasi-nano-particles in an ethanol aqueous solution, performing ultrasonic treatment, standing, and removing supernatant liquid to obtain a quasi-nano-particle suspension; and pouring the suspension into the chelating solution, stirring, heating, decomposing, calcining, grinding and screening to obtain the ternary iron-based oxygen carrier particles with the core-shell structure. The oxygen carrier with the core-shell structure can bear the high temperature of 800-950 DEG C, and the cycling stability, the reaction activity and the anti-sintering characteristic of the oxygen carrier are greatly superior to those of a homogeneous oxygen carrier when the oxygen carrier is applied to chemical looping hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a core-shell structured ternary iron-based oxygen carrier and a preparation method and application thereof, belonging to the field of chemical chain hydrogen production. Background Art

[0002] Hydrogen energy is a renewable energy source with great development potential. Compared with traditional fossil energy, hydrogen has a high calorific value per unit mass and is cleaner and more efficient. At present, methane steam reforming hydrogen production is still the most important method of hydrogen production in industry due to its mature technology and reliable operation of the equipment. However, the cost of methane steam reforming hydrogen production is high, the steam reforming reaction rate is slow, and the separation of CO2 in the hydrogen production process requires a lot of energy consumption. Therefore, a hydrogen production technology with lower cost, higher hydrogen production efficiency and relatively low CO2 capture energy consumption is urgently needed to be developed.

[0003] Chemical chain hydrogen production technology is a new type of hydrogen energy production technology. Its advantage is that it can achieve internal separation and capture of CO2 while producing high-purity hydrogen. The chemical chain hydrogen production system consists of three reactors, namely the fuel reactor, the steam reactor and the air reactor. In the fuel reactor, the oxygen carrier completely oxidizes the fuel into CO2 and H2O; then the reduced oxygen carrier is partially oxidized in the steam reactor and produces H2; finally, the partially oxidized oxygen carrier is completely oxidized in the air reactor.

[0004] Oxygen carrier is one of the most important factors affecting the performance of chemical chain hydrogen production. Its physicochemical properties directly affect the efficiency and purity of hydrogen production in the chemical chain hydrogen production process. Studies have found that Fe2O3 has significant advantages such as low cost, strong oxygen carrying capacity and environmental friendliness, and has good prospects for industrial application. However, single Fe2O3 will quickly lose its redox activity due to sintering, so Fe2O3 is usually loaded on a high temperature resistant inert carrier to enhance its cyclic stability. And because the deep reduction activity of Fe2O3 is poor, active carriers such as perovskite can be added to improve its deep reduction activity.

[0005] LaFeO3 is a classic ABO3-type perovskite with high oxygen storage and release capacity, reactivity and structural stability, which can enhance the deep reduction reaction activity and cyclic stability of the cycle process. ZrO2 is an inert carrier with good anti-sintering ability, which can effectively improve the cyclic stability of the oxygen carrier. Based on this, the researchers proposed a ternary iron-based oxygen carrier composed of Fe2O3, ZrO2 and LaFeO3, which showed better hydrogen production efficiency and cyclic stability than the binary oxygen carriers Fe2O3 / ZrO2 and Fe2O3 / LaFeO3 in the process of chemical chain hydrogen production. However, in the homogeneous oxygen carrier composed of Fe2O3, ZrO2 and LaFeO3, Fe ions will still migrate from the inside to the outside and enrich on the surface of the particles during the redox cycle, aggravating the sintering of the oxygen carrier. Therefore, relying solely on the synergistic effect between the inert carrier ZrO2 and the LaFeO3 perovskite still cannot solve the problem of migration, enrichment and sintering of iron ions from the inside to the outside in the iron-based oxygen carrier. To solve the problem of oxygen carrier sintering, scholars have proposed solutions ranging from modifying oxygen carrier components to constructing oxygen carrier particle structures. Core-shell structure particles are a type of physically modified high-functional material that is widely used in various fields, such as ion batteries, high-efficiency catalysts, and biomedicine. With the shielding effect of the shell in the core-shell structure, it is expected to provide a solution to the sintering problem of iron-based oxygen carriers in chemical chain hydrogen production. Summary of the invention

[0006] In view of the problem of iron ions in homogeneous iron-based oxygen carriers migrating to the particle surface for enrichment and the resulting sintering of the oxygen carriers in the process of chemical chain hydrogen production, the present invention provides a core-shell structured ternary iron-based oxygen carrier and a preparation method thereof and an application thereof in a chemical chain hydrogen production reaction, specifically a core-shell structured ternary iron-based oxygen carrier composed of three components: Fe2O3, LaFeO3 and ZrO2 and a preparation method and application thereof. By utilizing the core-shell structure and the excellent sintering resistance of ZrO2, as well as the excellent oxygen ion conductivity of LaFeO3, the redox reaction activity, cycle stability, sintering resistance and carbon deposition resistance of the iron-based oxygen carrier in chemical chain hydrogen production are improved to overcome the inherent defects of the iron-based oxygen carrier.

[0007] In order to solve the existing problems, the technical solution adopted by the present invention is:

[0008] A core-shell structured ternary iron-based oxygen carrier, wherein the core-shell structured ternary iron-based oxygen carrier particles have a particle size of 150-350 μm, the core body is a quasi-nano particle, and is composited with Fe2O3, ZrO2 and LaFeO3 in a mass ratio of 6:1:3.

[0009] As an improvement, the core-shell structure is a quasi-nanoscale Fe2O3 core particle coated with LaFeO3-ZrO2 as a shell or a quasi-nanoscale Fe2O3-ZrO2 core particle coated with LaFeO3 as a shell.

[0010] As an improvement, the particle sizes of the quasi-nanoscale Fe2O3-ZrO2 and Fe2O3 core particles are both 100-300 nm.

[0011] The preparation method of the core-shell structured ternary iron-based oxygen carrier comprises the following steps:

[0012] (1) dissolving a water-soluble salt of a core material in deionized water to obtain a mixed solution, heating the mixed solution to 40-70° C., adding an ammonia solution dropwise, adjusting the pH value to above 4.5, so that the metal ions in the solution are completely precipitated, and then aging the precipitate at 20-25° C., filtering to obtain a cake-like substance, further drying to obtain a block precursor, and then sequentially performing decomposition, calcination, and ball milling to obtain quasi-nano particles of the core material;

[0013] (2) dissolving a water-soluble salt of the shell material in deionized water, stirring to obtain a mixed solution, heating and adding citric acid dropwise, and further heating to obtain a chelating solution A;

[0014] (3) dispersing the core material quasi-nano particles of step (1) in an ethanol aqueous solution, ultrasonically treating for at least 60 min, and then standing for more than 6 h, removing the supernatant of the suspension to obtain a core material quasi-nano particle suspension B;

[0015] (4) Pour the core material quasi-nano particle suspension B into the chelating solution A, heat and stir evenly at 40-60°C, continue to heat to above 80°C and heat at a constant temperature, stir to evaporate the water to form a gel, and further dry to obtain a block-shaped honeycomb precursor, followed by decomposition, calcination, and sieving to obtain a core-shell structured ternary iron-based oxygen carrier particles.

[0016] As an improvement, the water-soluble salt of the core material in step (1) is one or more of a water-soluble iron salt, a water-soluble zirconium salt and a water-soluble lanthanum salt; the concentration of the ammonia solution is 25% to 28%, the aging time is 2 to 24 hours, the drying temperature is 100 to 110°C, and the drying time is more than 12 hours; the decomposition temperature is 350 to 400°C, and the decomposition time is more than 1 hour; the calcination temperature is 850 to 950°C, and the calcination time is more than 2 hours.

[0017] As a further improvement, the water-soluble iron salt is iron nitrate, iron sulfate or iron acetate, the water-soluble zirconium salt is zirconium nitrate, zirconium oxynitrate, zirconium sulfate or zirconium acetate, and the water-soluble lanthanum salt is lanthanum nitrate, lanthanum sulfate or lanthanum acetate.

[0018] As an improvement, the water-soluble salt of the shell material in step (2) is one or more of a water-soluble iron salt, a water-soluble zirconium salt and a water-soluble lanthanum salt; and the molar ratio of the citric acid to the total cations in the solution is 3:1.

[0019] As an improvement, in step (4), the drying temperature is 100-110°C, and the drying time is more than 12 hours; the decomposition temperature is 350-400°C, and the decomposition time is at least 1 hour; the calcination temperature is 850-950°C, and the calcination time is at least 2 hours.

[0020] The application of the above core-shell structured ternary iron-based oxygen carrier in chemical chain hydrogen production.

[0021] As an improvement, the temperature of the chemical chain hydrogen production reaction is 800-950°C.

[0022] When the core-shell structure ternary iron-based oxygen carrier of the present invention is used in the reaction of chemical chain hydrogen production, in the oxygen carrier reduction stage, the core-shell structure ternary iron-based oxygen carrier reacts with carbon-containing gas fuel, and the core-shell structure oxygen carrier is deeply reduced; in the steam oxidation stage, the reduced core-shell structure oxygen carrier reacts with water vapor to generate high-purity H2; in the air oxidation stage, the partially oxidized core-shell structure oxygen carrier reacts with air to achieve the cyclic regeneration of the oxygen carrier. During the oxygen carrier redox cycle, the shell layer composed of LaFeO3 and ZrO2 alone or together can inhibit the migration and enrichment of Fe elements from the inside of the oxygen carrier to the particle surface, inhibit the sintering of the oxygen carrier during the reaction, thereby improving the reaction activity and cycle stability of the oxygen carrier in the chemical chain hydrogen production cycle.

[0023] Beneficial effects:

[0024] Compared with the prior art, the core-shell structured ternary iron-based oxygen carrier of the present invention and its preparation method and application have the following significant advantages:

[0025] (1) The preparation method of the core-shell structure ternary iron-based oxygen carrier of the present invention is simple, no other impurity phases will appear during the synthesis process, and the synthesis cycle is short.

[0026] (2) The core-shell structured ternary iron-based oxygen carrier of the present invention can withstand high temperatures of 800 to 950° C. and has high reactivity and good cycle stability.

[0027] (3) The core-shell structured ternary iron-based oxygen carrier of the present invention achieves uniform coating of the quasi-nano oxygen carrier particles, thereby avoiding the migration and enrichment of iron ions from the inside to the outside, and thus has the characteristic of strong anti-sintering ability.

[0028] (4) During the redox cycle of the core-shell structured ternary iron-based oxygen carrier of the present invention, part of LaFeO3 reacts with ZrO2 to generate high-melting-point pyrochlore La2Zr2O7, which is beneficial to improving the sintering resistance and cycle stability of the core-shell structured ternary iron-based oxygen carrier.

[0029] (5) The core-shell structured ternary iron-based oxygen carrier of the present invention is used in the chemical chain hydrogen production reaction, and its hydrogen yield is as high as 5.61 mmol·g-1 , which is 41.6% higher than that of a homogeneous ternary iron-based oxygen carrier with the same mass fraction of each phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD diagrams of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1 and 2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2;

[0031] Figure 2 The particle size distribution diagram of Fe2O3, Fe2O3-ZrO2 and Fe2O3-LaFeO3 quasi-nano particles obtained by ball milling for 2 h in the preparation process of Examples 1, 2 and Comparative Example 1;

[0032] Figure 3 TEM images of the core-shell structured ternary iron-based oxygen carrier obtained in Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2, wherein (a) is Comparative Example 2 and (b) is Example 1;

[0033] Figure 4 H2-TPR graphs of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2;

[0034] Figure 5 The graphs are the variation of H2 yield (a) and H2 purity (b) in the steam oxidation stage at 850°C for the core-shell structure ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 as a function of the number of cycles;

[0035] Figure 6 The CO2 concentration (a) and H2 concentration (b) of the 15th cycle CO reduction stage of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2 at 850°C;

[0036] Figure 7 It is a graph showing the conversion rate of the oxygen carrier in the reduction stage during the 15th cycle at 850° C. for the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2;

[0037] Figure 8 The graph of the change of H2 yield and H2 purity during 50 redox cycles of the core-shell structure ternary iron-based oxygen carrier obtained in Example 1 at 850°C;

[0038] Fig. 9XRD patterns of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after cyclic reaction at 850°C, (a) Fe-La-Zr, (b) Fe@La-Zr, (c) Fe-La@Zr, (d) Fe-Zr@La;

[0039] Fig.10 SEM comparison of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after the cyclic reaction at 850°C; wherein, (a) fresh Fe-La-Zr sample, (b) Fe-La-Zr sample after 15 cycles, (c) fresh Fe@La-Zr sample, (d) Fe@La-Zr sample after 15 cycles, (e) fresh Fe-La@Zr sample, (f) Fe-La@Zr sample after 15 cycles, (g) fresh Fe-Zr@La sample, (h) Fe-Zr@La sample after 15 cycles;

[0040] Fig.11 It is a H2-TPR comparison diagram of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2 before and after cycling at 850°C; wherein, (a) Fe-La-Zr, (b) Fe@La-Zr, (c) Fe-La@Zr, (d) Fe-Zr@La;

[0041] Fig.12 XPS O1s spectra of the core-shell structure ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after cycling at 850°C; wherein, (a) Fe-La-Zr-fresh sample, (b) Fe-La-Zr-sample after 15 cycles, (c) Fe@La-Zr-fresh sample, (d) Fe@La-Zr-sample after 15 cycles, (e) Fe-La@Zr-fresh sample, (f) Fe-La@Zr-sample after 15 cycles, (g) Fe-Zr@La-fresh sample, (h) Fe-Zr@La-sample after 15 cycles;

[0042] Fig.13 The figure is a flow chart for preparing the core-shell structured ternary iron-based oxygen carrier of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0044] Example 1

[0045] A core-shell structured ternary iron-based oxygen carrier, with 30wt% LaFeO3 and 10wt% ZrO2 as the shell and 60wt% Fe2O3 as the core, 10g, is recorded as Fe@La-Zr (core@shell):

[0046] Weigh 30.36g of Fe(NO3)3·9H2O and dissolve it in deionized water, stir it magnetically, and get a mixed nitrate solution. After heating the mixed solution to 70℃ in a magnetic stirrer, slowly add ammonia solution as a precipitant to adjust the pH value of the solution to 4.5. Take the precipitate and age it at room temperature for 12h. Then use a Buchner funnel to filter the precipitate to get a cake, and dry it in an oven at 105℃ for 24h to get a block precursor. The precursor is then decomposed at 350℃ in a muffle furnace for 2h and calcined at 900℃ for 2h. Finally, the calcined Fe2O3 is placed in a planetary ball mill at 400r / min for 2h to obtain quasi-nanoparticles of Fe2O3.

[0047] Weigh 4.99g Fe(NO3)3·9H2O, 5.35g La(NO3)3·6H2O, and 3.49g Zr(NO3)4·5H2O, dissolve them in an appropriate amount of deionized water, place them in a magnetic stirrer, heat them to 30°C, and stir them for 30 minutes to fully dissolve the precursors to obtain a mixed nitrate solution; then add a calculated amount of citric acid (C6H7O8) to the solution to make the molar ratio of C6H7O8 to the total cations in the solution reach 3:1. Place the mixed solution in a magnetic stirrer, heat it to 50°C, and stir it for 30 minutes to obtain a chelating solution A.

[0048] Weigh 6 g of quasi-nanoparticle Fe2O3 and disperse it in an ethanol-water solution with an ethanol volume fraction of 60%. Ultrasonic treatment was performed for about 60 minutes to fully disperse the Fe2O3 quasi-nanoparticles. The suspension was allowed to stand for 6 hours, and finally the supernatant in the suspension was removed to obtain a quasi-nanoparticle Fe2O3 suspension B.

[0049] Pour suspension B into chelating solution A, heat the solution to 50°C in a magnetic stirrer and continue stirring for 30 minutes to mix the two solutions evenly, continue to heat to a constant 80°C, and stir the solution at this temperature for about 4.0 hours to evaporate the water to form a gel. The obtained gel was dried in a 105°C oven for 24 hours to obtain a block honeycomb oxygen carrier precursor, which was then decomposed at 350°C in a muffle furnace for 2 hours and calcined at 900°C for 2 hours. Finally, the calcined product was crushed and sieved with a standard sample sieve to obtain core-shell structured Fe@La-Zr oxygen carrier particles with a particle size range of 150-350μm.

[0050] Example 2

[0051] A core-shell structured ternary iron-based oxygen carrier, 10g of which is composed of 30wt% LaFeO3 as a shell and 10wt% ZrO2 and 60wt% Fe2O3 as a core, is denoted as Fe-Zr@La.

[0052] The specific operation process is the same as that of Example 1, except that:

[0053] For the preparation of quasi-nanoparticles, 30.36 g of Fe(NO3)3·9H2O and 3.49 g of Zr(NO3)4·5H2O were weighed.

[0054] When preparing chelating solution A, weigh 4.99 g Fe(NO3)3·9H2O and 5.35 g La(NO3)3·6H2O.

[0055] When preparing suspension B, the mass of quasi-nano Fe2O3-ZrO2 core particles was weighed to be 7 g.

[0056] Comparative Example 1

[0057] A core-shell structured ternary iron-based oxygen carrier, 10g of which is composed of 10wt% ZrO2 as a shell and 30wt% LaFeO3 and 60wt% Fe2O3 as a core, is denoted as Fe-La@Zr.

[0058] The specific operation process is the same as that of Example 1, except that:

[0059] For the preparation of quasi-nanoparticles, 35.35 g of Fe(NO3)3·9H2O and 5.35 g of La(NO3)3·6H2O were weighed.

[0060] When preparing chelating solution A, 3.49 g Zr(NO3)4·5H2O was weighed.

[0061] When preparing suspension B, the mass of quasi-nanoparticles was weighed to be 9 g.

[0062] Comparative Example 2

[0063] A homogeneous ternary iron-based oxygen carrier, specifically 10g of a homogeneous ternary iron-based oxygen carrier co-loaded with 30wt% LaFeO3 and 10wt% ZrO2, denoted as Fe-La-Zr.

[0064] The specific operation process is the same as that of Example 1, except that:

[0065] There is no need to prepare the Fe2O3 quasi-nanoparticle suspension in advance. Instead, 20.17 g Fe(NO3)3·9H2O, 5.35 g La(NO3)3·6H2O, and 3.49 g Zr(NO3)4·5H2O are dissolved together in chelating solution A.

[0066] The iron-based oxygen carriers obtained in Example 1-2 and Comparative Example 1-2 were subjected to X-ray diffraction tests, and the results were as follows: Figure 1 As shown in the figure, the four fresh oxygen carriers all have three phases of Fe2O3, ZrO2 and LaFeO3. The six main diffraction peaks observed at 2θ = 22.6°, 32.2°, 39.7°, 46.2°, 57.4° and 67.4° correspond to the perovskite structure of LaFeO3 (PDF75-0541), which match the diffraction angles corresponding to the characteristic crystal planes (101), (110), (111), (200), (211) and (220) of the standard card spectrum of LaFeO3 respectively; the diffraction peaks observed at 2θ = 24.2°, 33.2°, 35.7°, 40.9°, 49.5°, 54.1°, 62.5° and 64.0° correspond to Fe2O3 (PDF 73-2234), which match the diffraction angles corresponding to the characteristic crystal planes (110), (121), (-110), (120), (220), (231), (130) and (211) of Fe2O3 in the standard card spectrum; due to the low relative content of ZrO2, only a weak peak of ZrO2 can be observed at 2θ=31.8°; no phase related to Fe-Zr solid solution or La-Zr compound was observed. The above results show that the phase composition of the four oxygen carriers is the same, and the oxygen carrier containing only three phases of Fe2O3, LaFeO3 and ZrO2 was successfully synthesized in the experiment.

[0067] The particle size distribution of Fe2O3, Fe2O3-ZrO2 and Fe2O3-LaFeO3 quasi-nano particles obtained by ball milling for 2 h in the preparation process of Examples 1-2 and Comparative Example 1 is as follows: Figure 2 As shown in the figure, the particle size distribution of Fe2O3, Fe2O3-ZrO2 and Fe2O3-LaFeO3 quasi-nano core particles obtained by ball milling for 2h is relatively uniform, and their particle sizes are basically distributed in the range of 100-300nm, and the particle sizes of quasi-nano particles are mostly concentrated at 200nm. This shows that the target standard nanoparticles are obtained by ball milling for 2h, and these quasi-nano particles are approximately normally distributed in particle size, which lays a foundation for the further synthesis and research of the subsequent core-shell structure oxygen carrier.

[0068] The TEM images of the core-shell structured ternary iron-based oxygen carrier obtained in Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2 are shown in FIG. Figure 3 As shown. Figure 3 (a) It can be seen that the Fe-La-Zr oxygen carrier is a crystal with a random mixed morphology. Figure 3The TEM results in (b) clearly show that there is a boundary line between two different crystal phases at the edge of the Fe@La-Zr oxygen carrier. The inner crystal phase corresponds to Fe2O3(110) crystals, and the outer crystal phase corresponds to LaFeO3(211) crystals. No ZrO2 crystal phase is observed in the outer region, which is due to the low doping content of ZrO2 in the shell. The particle size of the inner layer of the oxygen carrier is about 150nm, which is consistent with the results. Figure 2 The results shown are consistent.

[0069] Example 3 Oxygen Carrier H2-TPR Evaluation

[0070] Taking Comparative Example 2 as the control group, the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 was evaluated by H2-programmed temperature reduction (H2-TPR). The test was performed on a chemical adsorption analyzer (Auto Chem 2920) produced by Micromeritics Instruments, Inc., USA; the amount of the oxygen carrier was 100 mg, and the reactor temperature was increased from 50°C to 1000°C at a heating rate of 10°C / min in an H2 / Ar atmosphere with a flow rate of 15 mL / min and a H2 volume fraction of 10%. The reaction time was about 100 min, and the reaction pressure was normal pressure. The change in the signal intensity of H2 consumption during the reaction was as shown in FIG. Figure 4 shown.

[0071] Figure 4 The H2-TPR result diagram of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2. According to the TPR experimental results, the H2-TPR diagrams of the four fresh oxygen carriers all contain three reduction peaks. Since the oxygen transmission capacity of Fe2O3 in the oxygen carrier is much higher than that of LaFeO3, these reduction peaks all come from the reduction process of Fe2O3. Usually, Fe2O3 undergoes a two-step reduction process in a H2 atmosphere, but the interaction between ZrO2 and Fe2O3 affects the reduction process of Fe2O3. Therefore, Fe2O3 exhibits a three-step reduction process in a H2 atmosphere, i.e., Fe2O3→Fe3O4→FeO→Fe. The three-step reduction process corresponds to the three reduction peaks of α, β and γ in the H2-TPR spectrum. The peak temperature of the α reduction peak of the Fe-La-Zr oxygen carrier is 455°C, while the peak temperatures of the α reduction peaks of the Fe@La-Zr, Fe-La@Zr and Fe-Zr@La oxygen carriers are 460°C, 496°C and 465°C, respectively. The peak temperatures of the α reduction peaks of the three core-shell structure oxygen carriers are higher than those of the homogeneous oxygen carriers. The peak temperatures of the β and γ reduction peaks of the Fe@La-Zr oxygen carrier are significantly lower than those of the other three oxygen carriers, showing excellent reduction activity, as shown in Table 1.

[0072] Table 1 H2 consumption of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-3 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 1 during the H2-TPR process

[0073]

[0074] Table 1 shows the H2 consumption of different materials during the H2-TPR process. It can be seen from the table that the order of H2 consumption of the four oxygen carriers is: Fe@La-Zr>Fe-Zr@La>Fe-La-Zr>Fe-La@Zr. The above results show that the core-shell structure basically does not inhibit the reduction activity of the oxygen carrier, and the reduction activity of the oxygen carrier can be further improved under a certain construction type; among them, the Fe@La-Zr oxygen carrier has the best reduction activity, because the LaFeO3 in the shell of the oxygen carrier promotes the transmission of electrons and oxygen ions, while ZrO2 plays a role in inhibiting the sintering of the oxygen carrier particles.

[0075] Example 4 Hydrogen yield and purity test of multiple cycles of steam oxidation with different oxygen carriers

[0076] The chemical chain hydrogen production cycle reaction activity and stability test was carried out on a fixed bed reactor using the core-shell structured ternary iron-based oxygen carrier obtained in Examples 1-3 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 1. The amount of oxygen carrier used is 1.0 g, the particle size is 150-350 μm, and the temperature during the entire cycle is a constant temperature of 850°C; the composition of the fuel gas in the oxygen carrier reduction stage is CO and N2, with a total flow rate of 220 mL / min (of which the CO flow rate is 20 mL / min, and the N2 flow rate is 200 mL / min), the reduction time is 10 min, and after the end, CO is turned off, and N2 (flow rate 300 mL / min) is purged for about 15 min; then a mixed gas of water vapor and N2 is introduced, with a total flow rate of 200.19 mL / min (of which water vapor is 20 mL / min, and N2 is 200 mL / min). The steam flow rate is 0.19mL / min, the N2 flow rate is 200mL / min), the water vapor oxidation time is 5min, the water vapor is turned off after the end, and it is purged with N2 (flow rate 300mL / min) for about 5min; the gas composition in the air oxidation stage is O2 and N2, the total flow rate is 230mL / min (of which the O2 flow rate is 30mL / min, and the N2 flow rate is 200mL / min), and the oxidation time is 5min, in order to achieve the regeneration of the oxygen carrier; the above reaction steps are repeated 15 times to test the reaction activity and stability of the oxygen carrier. The reactor outlet gas is tested online with a flue gas analyzer after the water vapor is removed by a molecular sieve. The results of H2 yield and H2 purity are shown in Figure 5 shown.

[0077] Figure 5The graphs are the variation of H2 yield and H2 purity with the number of cycles in the steam oxidation stage at 850°C for the core-shell structure ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2; wherein (a) is the variation of H2 yield with the number of cycles, and (b) is the variation of H2 purity with the number of cycles. Figure 5 In (a), the H2 yields of the four oxygen carriers will undergo an "activation" process in the second cycle, resulting in an increase in the H2 yield. In the subsequent 3-15 cycles, the H2 yields all show a downward trend. For the homogeneous oxygen carrier Fe-La-Zr, the H2 yield decreases very rapidly during the 3-15 cycles, and the H2 yield of the 15th cycle decreases by 40.08% compared with the second cycle. The H2 yields of Fe@La-Zr, Fe-La@Zr, and Fe-Zr@La oxygen carriers decrease less during the 3-15 cycles, and the H2 yields tend to stabilize after 5 cycles; the average H2 yields of Fe-La-Zr, Fe@La-Zr, Fe-La@Zr, and Fe-Zr@La in 15 cycles are 3.96mmol·g -1 , 5.61mmol·g -1 , 4.07mmol·g -1 , and 4.99mmol·g -1 The average H2 yield is in the following order: Fe@La-Zr>Fe-Zr@La>Fe-La@Zr>Fe-La-Zr, which indicates that a specific spatial composition distribution can significantly increase the reactivity and cyclic stability of the oxygen carrier. The H2 yield of Fe-La@Zr is close to that of the homogeneous oxygen carrier because this structure limits the oxygen ion transport capacity of LaFeO3.

[0078] Depend on Figure 5 (b) It can be seen that the average H2 purity of the four oxygen carriers can reach more than 98.5% during 15 cycles. The average H2 purity of Fe-La-Zr, Fe@La-Zr, Fe-La@Zr and Fe-Zr@La oxygen carriers during 15 cycles are 98.94%, 99.34%, 98.96% and 99.00% respectively. The order of average H2 purity from large to small is: Fe@La-Zr>Fe-Zr@La>Fe-La@Zr>Fe-La-Zr, which is the same as the order of H2 yield. This shows that compared with homogeneous oxygen carriers, core-shell structure oxygen carriers (especially Fe@La-Zr) have higher resistance to carbon deposition.

[0079] Figure 6Schematic diagram of the CO2 concentration in the CO reduction stage and the H2 concentration in the water vapor oxidation stage of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2, respectively. Figure 6 In (a), Fe-La-Zr, Fe@La-Zr, Fe-La@Zr and Fe-Zr@La oxygen carriers all reached CO2 concentration peaks within 1.4 minutes. The CO2 concentration peaks of the four oxygen carriers were 7.64%, 8.95%, 8.48% and 8.97%, respectively. The CO2 concentration peak of the core-shell structure oxygen carrier was significantly higher than that of the homogeneous oxygen carrier. After the CO2 concentration reached the peak, the CO2 concentration of the four oxygen carriers showed a downward trend. After 1.2 minutes, the CO2 concentration of the Fe@La-Zr oxygen carrier was always higher than that of the other three.

[0080] from Figure 6 As can be seen in (b), the H2 concentration of all oxygen carriers rises rapidly during the steam oxidation stage, and then reaches the peak H2 concentration at about 0.4 minutes. Since the Fe@La-Zr oxygen carrier has the highest degree of reduction in the CO reduction stage, its H2 concentration peak during the steam oxidation stage is much higher than the other three, at 56.71%. The Fe-La-Zr oxygen carrier has the lowest H2 concentration peak, at only 36.77%. After the H2 concentration reaches the peak, the CO2 concentration of the four oxygen carriers decreases rapidly. In the 0.7-2.1 minutes, the H2 concentrations of the Fe@La-Zr and Fe-Zr@La oxygen carriers are similar, and significantly higher than those of the Fe-La-Zr and Fe-La@Zr oxygen carriers.

[0081] Figure 7 The conversion rate curve of the oxygen carrier in the reduction stage of the core-shell structure ternary iron-based oxygen carrier obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2 at 850°C in the 15th cycle. As can be seen from the figure, the conversion rate of Fe@La-Zr and Fe-Zr@La oxygen carriers reaches 33.3% after about 5.4 minutes, while the conversion rate of Fe-La-Zr and Fe-La@Zr oxygen carriers reaches 33.3% after about 7 minutes, which indicates that Fe2O3 in all oxygen carriers can be reduced to FeO / Fe state during the reduction process. After the reduction stage, the conversion rate of Fe@La-Zr oxygen carrier was the highest, which was 52.0%. It was calculated that 28.1% of Fe2O3 in the oxygen carrier was reduced to Fe elemental state, and 71.9% of Fe2O3 was reduced to FeO state; the conversion rate of Fe-La-Zr oxygen carrier was the lowest, which was 40.8%, indicating that 11.3% of Fe2O3 in the oxygen carrier was reduced to Fe elemental state, and 88.7% of Fe2O3 was reduced to FeO state; the reduction degree of Fe@La-Zr oxygen carrier was much higher than that of Fe-La-Zr oxygen carrier.

[0082] Example 5 Long-term cyclic stability test of core-shell structured ternary iron-based oxygen carrier

[0083] The core-shell structure ternary iron-based oxygen carrier obtained in Example 1 was used to carry out a long-cycle reaction activity and stability test of chemical chain hydrogen production in a fixed bed reactor; the reaction activity and stability of the ternary iron-based oxygen carrier were tested 50 times according to the reaction steps in Example 5, and the reactor outlet gas was tested online with a gas analyzer. The results are as follows Figure 8 shown.

[0084] Figure 8 The graph of H2 yield and H2 purity during 50 redox cycles of the core-shell ternary iron-based oxygen carrier obtained in Example 1 at 850°C is shown in the figure. As can be seen from the figure, due to the activation of the oxygen carrier, the H2 yield increases in the second cycle; it shows a downward trend in the 3rd to 18th cycles, from 6.06mmol·g in the second cycle to 1.3mmol·g in the 18th cycle. -1 The decrease was to 4.97 mmol·g in the 18th cycle. -1 ; In the 19th to 50th cycles, the H2 yield entered a relatively stable state, and the average H2 yield during the 50 cycles was 4.50 mmol·g -1 , indicating that the structure of the oxygen carrier tends to be stable. From the perspective of H2 purity, the H2 purity fluctuates in the range of 99.2%-99.8% during 50 cycles, and its average H2 purity is 99.49%. In summary, the Fe@La-Zr oxygen carrier still has good redox stability after 50 cycles, and can maintain a stable H2 yield and H2 purity. It is an oxygen carrier suitable for long-term cycles of chemical chain hydrogen production.

[0085] Fig. 9 The XRD patterns of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after the cyclic reaction at 850°C. Fig. 9 As shown in (a), (b), (c), and (d), only three phases, Fe2O3, LaFeO3, and ZrO2, exist in the four fresh oxygen carriers, while in the air-oxidized oxygen carrier after recycling, high-intensity diffraction peaks of pyrochlore-type La2Zr2O7 can be observed, the peak intensity of LaFeO3 becomes weaker, and ZrO2 is not observed. This is because Fe2O3 is reduced to Fe during the reduction process of the oxygen carrier, and the catalytic effect of Fe causes LaFeO3 to react with ZrO2 to generate La2Zr2O7. For the reduced oxygen carriers after recycling, Fe@La-Zr, Fe-La@Zr, and Fe-Zr@La are all deeply reduced to FeO and Fe states; while part of the Fe2O3 in the Fe-La-Zr oxygen carrier cannot be deeply reduced to FeO and Fe states.

[0086] Fig.10 The SEM comparison diagram of the core-shell structure ternary iron-based oxygen carrier obtained in Example 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carrier obtained in Comparative Example 2 before and after the cyclic reaction at 850°C. Fig.10 (a), (c), (e) and (g) show that before the cycle, the surfaces of the four oxygen carriers are evenly covered with particles of uniform size. The particle size of the surface particles is about 150-300nm, and a porous structure is formed on the surface of the oxygen carrier particles. The porous structure can promote the diffusion of the reaction gas into the interior of the particles during the reaction. Furthermore, the particle size of the Fe-La-Zr oxygen carrier surface particles is slightly smaller than that of the other three oxygen carriers. This is because the core quasi-nanoparticles of the core-shell structure oxygen carrier have a larger particle size, and the smaller particle size of the Fe-La-Zr oxygen carrier can increase its specific surface area, resulting in the α reduction peak of the Fe-La-Zr oxygen carrier in H2-TPR being lower than the other three. After 15 cycles, there are obvious differences in the apparent morphology of the four oxygen carriers. For Fig.10 (b) After the cycle of Fe-La-Zr oxygen carrier, the particles on the surface of the oxygen carrier particles are no longer evenly distributed, but are complexed together due to severe sintering, and the porous structure on the surface of the oxygen carrier disappears, thereby hindering the diffusion of the reaction gas into the interior of the oxygen carrier particles and reducing its reaction activity; Fig.10 After the cycle in (d), the surface of the Fe@La-Zr oxygen carrier particles was slightly sintered, and the surface particle size was about 200-350nm. In addition, the surface of the oxygen carrier still retained a large number of vents, which indicates that ZrO2 and LaFeO3 as shells can greatly improve the anti-sintering properties of the oxygen carrier, thereby improving the cyclic stability of the oxygen carrier in chemical chain hydrogen production. Fig.10 The sintering degree of the recycled Fe-La@Zr and Fe-Zr@La oxygen carriers in (f) and (g) is between that of Fe-La-Zr and Fe@La-Zr oxygen carriers. The particles on the surface of the oxygen carriers are sintered and complexed to form particles with a particle size of about 250-400nm, but the surface of the oxygen carriers still retains a good pore structure. The above results show that the core-shell structure oxygen carrier has a high sintering resistance, among which the Fe@La-Zr oxygen carrier exhibits the best sintering resistance.

[0087] Fig.11The H2-TPR comparison chart of the core-shell structure ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after cycling at 850°C. Compared with the fresh oxygen carriers, the peak temperatures of the α, β and γ reduction peaks of the four oxygen carriers after 15 cycles of reaction increased. This is because the four oxygen carriers all produced varying degrees of sintering during the cycle, resulting in a weakening of the oxygen carrier reactivity; after cycling, the reduction peak temperatures of Fe@La-Zr and Fe-Zr@La oxygen carriers were lower than those of Fe-La-Zr and Fe-La@Zr oxygen carriers, which indicates that adding LaFeO3 as the shell layer of the core-shell structure oxygen carrier can promote the transmission capacity of lattice oxygen, thereby improving the reactivity of the oxygen carrier.

[0088] Fig.12 The XPS O1s spectra of the core-shell structured ternary iron-based oxygen carriers obtained in Examples 1-2 and Comparative Example 1 and the homogeneous ternary iron-based oxygen carriers obtained in Comparative Example 2 before and after cycling at 850°C. The three sub-peaks of the oxygen element were fitted, namely lattice oxygen (OI), oxygen vacancy (OII) and surface adsorbed oxygen (OIII). The relative contents of the three oxygens are shown in Table 2.

[0089] Table 2 Relative contents of oxygen species in Fe-La-Zr, Fe@La-Zr, Fe-La@Zr and Fe-Zr@La oxygen carriers

[0090]

[0091] The oxygen vacancies in the oxygen carrier are conducive to the adsorption of reactants and the dissociation of products. It can be seen from Table 2 that the relative order of lattice oxygen, oxygen vacancies and surface adsorbed oxygen before and after the reaction of the four oxygen carriers is: lattice oxygen > oxygen vacancies > surface adsorbed oxygen; for the samples after 15 cycles of the four oxygen carriers, the oxygen vacancy ratios of all oxygen carriers showed a downward trend, and there was a large difference in the oxygen vacancy ratios of the four oxygen carriers. The oxygen vacancy ratios of the oxygen carriers after the cycle were in the following order from large to small: Fe@La-Zr>Fe-La@Zr>Fe-Zr@La>Fe-La-Zr, indicating that the core-shell structured oxygen carrier still maintained a high oxygen vacancy concentration after 15 cycles, thereby improving the lattice oxygen transmission capacity, reaction activity and cycle stability of the oxygen carrier.

[0092] In summary, the preparation method of the core-shell structured ternary iron-based oxygen carrier of the present invention is simple, no other impurity phases will appear during the synthesis process, and the synthesis cycle is short. The H2 yield of the prepared Fe@La-Zr oxygen carrier (with LaFeO3-ZrO2 as the shell and Fe2O3 as the core) is higher than that of other core-shell structured oxygen carriers or homogeneous oxygen carriers composed of three components; this is attributed to the fact that on the one hand, the LaFeO3 in the shell material can improve the lattice oxygen conductivity in the iron-based oxygen carrier and promote the migration of oxygen ions from the inside of the Fe2O3 quasi-nanoparticles to the surface of the oxygen carrier particles, and on the other hand, the anti-sintering performance of the ZrO2 in the shell material can improve the cyclic stability of the oxygen carrier.

[0093] The present invention and its embodiments are described schematically above, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and makes a structural method and an embodiment similar to the technical solution without creative design without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A core-shell structured ternary iron-based oxygen carrier, characterized in that: The core-shell structured ternary iron-based oxygen carrier particles have a particle size of 150-350 μm, the core body is a quasi-nano particle, and is composited with Fe2O3, ZrO2 and LaFeO3 in a mass ratio of 6:1:

3.

2. The core-shell structured ternary iron-based oxide according to claim 1, characterized in that: The core-shell structure is a structure in which LaFeO3-ZrO2 is used as a shell to cover quasi-nanoscale Fe2O3 core particles or LaFeO3 is used as a shell to cover quasi-nanoscale Fe2O3-ZrO2 core particles.

3. The core-shell structured ternary iron-based oxide according to claim 2, characterized in that: The particle sizes of the quasi-nanoscale Fe2O3-ZrO2 and Fe2O3 core particles are both 100-300nm.

4. A method for preparing a core-shell structured ternary iron-based oxygen carrier according to claims 1-3, characterized in that: The following steps are involved: (1) dissolving a water-soluble salt of a core material in deionized water to obtain a mixed solution, heating the mixed solution to 40-70° C., adding an ammonia solution dropwise, adjusting the pH value to above 4.5, so that the metal ions in the solution are completely precipitated, and then aging the precipitate at 20-25° C., filtering to obtain a cake-like substance, further drying to obtain a block precursor, and then sequentially performing decomposition, calcination, and ball milling to obtain quasi-nano particles of the core material; (2) dissolving a water-soluble salt of the shell material in deionized water, stirring to obtain a mixed solution, heating and adding citric acid dropwise, and further heating to obtain a chelating solution A; (3) dispersing the core material quasi-nano particles of step (1) in an ethanol aqueous solution, ultrasonically treating for at least 60 min, and then standing for more than 6 h, removing the supernatant of the suspension to obtain a core material quasi-nano particle suspension B; (4) Pour the core material quasi-nano particle suspension B into the chelating solution A, heat and stir evenly at 40-60°C, continue to heat to above 80°C and heat at a constant temperature, stir to evaporate the water to form a gel, and further dry to obtain a block-shaped honeycomb precursor, followed by decomposition, calcination, and sieving to obtain a core-shell structured ternary iron-based oxygen carrier particles.

5. The preparation method according to claim 4, characterized in that: The water-soluble salt of the core material in step (1) is one or more of a water-soluble iron salt, a water-soluble zirconium salt and a water-soluble lanthanum salt; the concentration of the ammonia solution is 25% to 28%, the aging time is 2 to 24 hours, the drying temperature is 100 to 110° C., and the drying time is more than 12 hours; the decomposition temperature is 350 to 400° C., and the decomposition time is more than 1 hour; the calcination temperature is 850 to 950° C., and the calcination time is more than 2 hours.

6. The preparation method according to claim 5, characterized in that: The water-soluble iron salt is iron nitrate, iron sulfate or iron acetate, the water-soluble zirconium salt is zirconium nitrate, zirconium oxynitrate, zirconium sulfate or zirconium acetate, and the water-soluble lanthanum salt is lanthanum nitrate, lanthanum sulfate or lanthanum acetate.

7. The preparation method according to claim 4, characterized in that: The water-soluble salt of the shell material in step (2) is one or more of a water-soluble iron salt, a water-soluble zirconium salt and a water-soluble lanthanum salt; the molar ratio of the citric acid to the total cations in the solution is 3:

1.

8. The preparation method according to claim 4, characterized in that: In step (4), the drying temperature is 100-110° C., and the drying time is more than 12 hours; the decomposition temperature is 350-400° C., and the decomposition time is at least 1 hour; the calcination temperature is 850-950° C., and the calcination time is at least 2 hours.

9. Use of the core-shell structured ternary iron-based oxygen carrier according to claims 1-3 in chemical chain hydrogen production.

10. The use according to claim 9, characterized in that: The temperature of the chemical chain hydrogen production reaction is 800-950°C.

Citation Information

Patent Citations

  • Method for preparing aryl oxygen-containing compound by catalytically oxidizing lignin through core-shell catalyst

    CN105693473A

  • Preparation method and application of high-temperature composite phase change regenerative oxygen carrier of iron lanthanum oxide-(copper-aluminum@alumina)

    CN109126803A

  • Preparation method of core-shell-shaped nano composite metal oxide

    CN109626438A

  • Heterojunction core-shell LaFeO3@g-C3N4 nanocomposite material, preparation method and application thereof

    CN110327855A

  • Ternary iron-based oxygen carrier as well as preparation method and application thereof

    CN117696063A